2018
DOI: 10.1016/s1569-9056(18)31079-0
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital tuberculosis: The cause of ineffective antibacterial therapy for urinary tract infections

Abstract: Background: Urogenital tuberculosis (UGTB) is one of the great imitators; it is commonly masked by urinary tract infections (UTIs). We aimed to estimate how many UGTB patients were among patients with a long history of UTIs. Material and Methods: A total of 244 patients with recurrent UTIs and suspected UGTB were enrolled in an open, noncomparative prospective study. Their urine and expressed prostate secretion or ejaculate were cultured (a total of 1446 samples), and 421 isolates with growth of ⩾10 4 colony-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…2) Urine tests Smear microscopy of urine refers to the microscopic examination for detecting acid-fast bacilli (AFB) performed by Ziehl-Neelsen staining, which is regarded as the first-line test for UGTB [32,33]. Ye et al reported that smear microscopy possessed poor sensitivity value of 9.8%.…”
Section: Laboratory Investigations 1) the Tuberculin Skin Testmentioning
confidence: 99%
“…2) Urine tests Smear microscopy of urine refers to the microscopic examination for detecting acid-fast bacilli (AFB) performed by Ziehl-Neelsen staining, which is regarded as the first-line test for UGTB [32,33]. Ye et al reported that smear microscopy possessed poor sensitivity value of 9.8%.…”
Section: Laboratory Investigations 1) the Tuberculin Skin Testmentioning
confidence: 99%